IMPLEMENTASI IDE KESEIMBANGAN DALAM PEMBANGUNAN HUKUM PIDANA INDONESIA BERBASIS NILAI-NILAI PANCASILA - Ira Alia Maerani (Jurnal Pembaharuan Hukum, 2016)
Criminal Law Science consists of the  Criminal Law Material (consisting of the Code of Penal (Penal Code=KUHP) and Act Outside the Criminal Code), Formal Criminal Law (Code of Criminal Law), and the Law of Criminal Execution. Code Penal (Penal Code) is derived from the Wetboek van Strafrecht voor Nederlands Indie (WvSvNI). Criminal Code (WvSNI) is a legal product "foreign" Dutch colonial administration which is not in accordance with the values espoused Indonesian nation and not in accordance with the conditions of the Indonesian nation freed with Pancasila as the foundation philosophy of legal development in Indonesia. Issues to be studied in this paper about the Pancasila philosophy approach in development efforts in the Indonesian criminal law and the implementation of the idea of balance in the development of criminal law in Indonesia are based on the values Pancasila. Research done by digging the values of Pancasila, the value on God particularly those contained in the Law of Islam (as a religion writer and the religion professed by the majority of the people of Indonesia), the value of humanity, unity, democracy, and social justice to change ideas/concepts of foreign laws that are incompatible with the basic philosophy of Pancasila. This study uses normative juridical methodology as in finding the data will be examined to the text of scripture, law and legal literature.